Deep Integration and UK-EU Trade Relations - Mulabdic, Alen; Osnago, Alberto; Ruta, Michele (World Bank, Washington, DC, 2017)
This paper studies the impact of deep agreements on United Kingdom-European Union trade relations. A standard gravity model is applied to assess the effect that European Union membership had on the United Kingdom's trade. The paper uses new information on the content of trade agreements to build a measure of "depth" based on the number of provisions the agreements cover. The analysis relies on information on goods, services, and value-added trade from the World Input Output Database. Deep trade agreements are found to increase goods and services trade by 42 percent, and value-added trade by 14 percent on average. European Union membership had a particularly strong effect on United Kingdom's services and global value chain trade. Because of its membership, the United Kingdom's services trade more than doubled, and the country's backward and forward participation in global value chains increased by more than 30 percent each. The paper uses these estimates to evaluate the future of United Kingdom-European Union trade under different scenarios. The findings show that United Kingdom-European Union trade declines under all scenarios, ranging between 6 and 28 percent for trade in value added. This drop is sharper (particularly for services and global value chain trade) the lower is the depth of the future arrangement relative to the depth of the European Union agreement. As trade flows adjust slowly to changes in trade costs, these effects are expected to emerge over time. But the trade-off between the depth of trade agreements and trade intensity will delimit policy choices going forward.